2016
DOI: 10.1007/s13277-016-4860-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells induced activation of nuclear factor κB signaling protects non-Hodgkin’s B lymphoma cells from apoptosis

Abstract: The microenvironment encompassing a variety of non-malignant cells in close proximity with malignant tumor cells has been well known to significantly affect the behavior of tumor cells. In this study, we therefore studied the mechanism of bone marrow stromal cells in protection of lymphoma cells from spontaneous apoptosis. We demonstrated that adhesion of the freshly isolated lymphoma B cells to bone marrow stromal cells or freshly isolated lymphoma stromal cells inhibited B cell spontaneous apoptosis in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…We therefore concluded that Notch pathway activation correlates with tumor cell proliferation, as shown by previous studies [34, 35]. Regarding chemoresistance, lymphoma cells cultured alone were more sensitive to lymphoma cells from the coculture system, as previous studies indicated [36]. But Notch-bearing adherent lymphoma cells did not show superiority to suspended lymphoma cells in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We therefore concluded that Notch pathway activation correlates with tumor cell proliferation, as shown by previous studies [34, 35]. Regarding chemoresistance, lymphoma cells cultured alone were more sensitive to lymphoma cells from the coculture system, as previous studies indicated [36]. But Notch-bearing adherent lymphoma cells did not show superiority to suspended lymphoma cells in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, cancer stem cells or the tumor-initiating cells of BCL maintain their tumorigenic potential via interplay with the TME [15, 16]. Previous studies have demonstrated that the protective effect of the TME was mediated through tumor-stroma cell interactions, especially direct cell-to-cell contact between tumor cells and stromal cells [17-19]. It is recognized that the Notch pathway is a canonical signal-transducing pathway mediating cell-to-cell communication.…”
Section: Introductionmentioning
confidence: 99%
“…However, accumulating evidence indicates that MSCs act as pro-tumor factors that interact with lymphoma cells and promote lymphoma growth, survival, and drug-resistance through multiple mechanisms [8, 25]. Recent studies show that hATMSCs or hBMSCs promote growth and drug-resistance in Burkitt lymphoma cells or DLBCL cells in vitro or in vivo [9, 10, 26, 27]. Here, we found that hBMSCs promoted the growth and drug-resistance of SU-DHL-2 and SU-DHL-4 cells in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the interaction between BAFF and its receptors on lymphoma and normal B cells, which promotes I κ B α degradation and processes of NF- κ B2, respectively. 39 , 40 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%